Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) and Cyclic ADP-Ribose (cADPR) Mediate Ca(2+) Signaling in Cardiac Hypertrophy Induced by β-Adrenergic Stimulation - Gul, Rukhsana (PLoS One, 2016)
Ca(2+) signaling plays a fundamental role in cardiac hypertrophic remodeling, but the underlying mechanisms remain poorly understood. We investigated the role of Ca(2+)-mobilizing second messengers, NAADP and cADPR, in the cardiac hypertrophy induced by β-adrenergic stimulation by isoproterenol. Isoproterenol induced an initial Ca(2+) transients followed by sustained Ca(2+) rises. Inhibition of the cADPR pathway with 8-Br-cADPR abolished only the sustained Ca(2+) increase, whereas inhibition of the NAADP pathway with bafilomycin-A1 abolished both rapid and sustained phases of the isoproterenol-mediated signal, indicating that the Ca(2+) signal is mediated by a sequential action of NAADP and cADPR. The sequential production of NAADP and cADPR was confirmed biochemically. The isoproterenol-mediated Ca(2+) increase and cADPR production, but not NAADP production, were markedly reduced in cardiomyocytes obtained from CD38 knockout mice. CD38 knockout mice were rescued from chronic isoproterenol infusion-induced myocardial hypertrophy, interstitial fibrosis, and decrease in fractional shortening and ejection fraction. Thus, our findings indicate that β-adrenergic stimulation contributes to the development of maladaptive cardiac hypertrophy via Ca(2+) signaling mediated by NAADP-synthesizing enzyme and CD38 that produce NAADP and cADPR, respectively.